Amino multi-walled carbon nanotubes further improve the thermal conductivity of boron nitride/liquid crystal epoxy resin composites - T. F. Qin; H. Wang; J. He; Q. Q. Qu; Y. S. Da; X. Y. Tian (eXPRESS Polymer Letters)
In this work, we introduced highly thermally conductive and fibrous amino multi-walled carbon nanotubes (MCNT-NH2) into hexagonal boron nitride/liquid crystal epoxy resin (h-BN/LCER) composites to improve the thermal conductivity of the composites. First, we prepared hexagonal boron nitride@amino multi-walled carbon nanotubes (h-BN@MCNT-NH2) hybrid fillers. Then, the amino group in the hybrid filler participated in the curing process of the epoxy resin to prepare hexagonal boron nitride@amino multi-walled carbon nanotubes/liquid crystal epoxy resin (h-BN@MCNTNH2/LCER) composites. Subsequently, its thermal conductivity was tested and analyzed using the Agari’s model and microstructure of the composites, and we can come to conclude that the thermal conductivity of h-BN@MCNT-NH2/LCER composites is higher than that of h-BN/LCER at the same filler content. The main reason is that the addition of MCNT-NH2 plays a role in increasing the thermal conduction path of h-BN/LCER composites and decreasing the large interface thermal resistance of fillers and resin matrix. Finally, the usability and thermal conductivity of h-BN@MCNT-NH2/LECR composites were verified by light-emitting diode (LED) lamps. The temperature of LED lamp using 50% h-BN@MCNT-NH2/LCER composites was eventually stabilized at 27.7 °C, it is expected that 50% h-BN@MCNT-NH2/LCER composites will be used in LED electronic products.